Photodegradation of the pharmaceuticals amoxicillin, bezafibrate and paracetamol by the photo-Fenton process - Application to sewage treatment plant effluent - Trovo, Alam Gustavo [UNESP]; Santos Melo, Silene Alessandra [UNESP]; Pupo Nogueira, Raquel Fernandes [UNESP] (Elsevier B.V. Sa, 2008)
Photodegradation of the pharmaceuticals amoxicillin (AMX), bezafibrate (BZF) and paracetamol (PCT) in aqueous solutions via the photo-Fenton process was investigated under black-light and solar irradiation. The influences of iron source, initial H2O2 concentration and matrix (distilled water and sewage treatment plant effluent) on degradation efficiency were discussed in detail. The results showed that (i) the degradation of the drugs was favored in the presence of potassium ferrioxalate (FeOx) in comparison to Fe(NO3)(3): (ii) the increase of the H2O2 concentration improved the efficiency of AMX and BZF oxidation; however, the same was not observed for PCT: (iii) the influence of the matrix was observed for the degradation of BZF and PCT: (iv) under solar irradiation, the oxidation of the BZF and PCT is faster than under black-light irradiation. All these pharmaceuticals can be efficiently degraded employing the process evaluated. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: advanced oxidation process; sewage treatment plant; antibiotic; anti-inflammatory; lipid regulator